STUDENTS IN THE PROCESS OF TRAINING (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The determination of the goals and objectives of educational activities for the development of mathematical skills of students is the main direction of modern pedagogy. It is a process that requires the teacher to deeply analyze and understand the individual characteristics of each student, as well as develop a flexible and differentiated curriculum.